I Feel Less Judged, so I Speak More : Introverted Students' Response on Online Learning Platforms in Speaking Class - Nuning Wahyu Astuti (JETLe (Journal of English Language Teaching and Learning), 2021)
As one of the productive skills in English Language, speaking has always been associated with extroverted people. However, during this online learning, introverted students gain autonomy which allows them to express ideas freely. The article used a mixed-method to collect data. The result revealed 70,33% of the total participants were introverted students. In answering the questionnaire, the participants agreed on 6 items and disagreed on 3 items. The article serves as a basis for instructors, academicians, and researchers to provide the most suitable online learning platforms for all types of students.